Emotional Skills and Interpersonal Conflict: Testing the Role of Teachers’ Emotional Intelligence - Valente, Sabina (2023)
Conflict is emotionally conceived and managed by emotions. Thus, for teachers’ to be successful in managing classroom conflict have to start by being successful in managing their own emotions. Studies, in other workplaces, show the relationship between emotional intelligence and conflict management. However, there is a lack of studies that relates teachers’ emotional intelligence with conflict management. To bridge this gap, this study aimed to investigate how teachers’ emotional intelligence influences the use of strategies to manage conflict in the classroom. A total of 797 teachers (from the 1st to the 2nd cycle of basic education) working in Portuguese schools completed measures of demographic information, emotional intelligence, and conflict management. Using structural equation modeling, results revealed that teachers’ emotional intelligence influences the choice of the most appropriate strategies to manage conflicts in the classroom. Therefore, considering the significance of teachers’ emotional intelligence in classroom conflict, it is necessary to integrate emotional skills in the teachers’ training (in pre-service, and in-service teachers) as essential skills for teaching practice.